CENTRAL BANK OPEN MARKET POLICY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The monetary and credit system is one of the indispensable and stable directions of the economy of every country. This article describes in detail the policy of the Central Bank in the open market.